2019
DOI: 10.1007/s40430-019-1748-1
|View full text |Cite
|
Sign up to set email alerts
|

Vibration attenuation of rotor-bearing systems using smart electro-rheological elastomer supports

Abstract: Nowadays, capability of safe operation sufficiently away from the critical speeds is one of the most important design requirements of rotating machineries. The focus of this paper is the application of smart electro-rheological (ER) elastomers to rotor dynamics field to reduce the vibration level of a rotor system. A Jeffcott rotor, supported via two bearings at both ends augmented with ER elastomers, is considered. A finite element approach, based on the Rayleigh beam theory, is used to model the dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In this research work, the ERE material is assumed to be an isotropic material, as proposed by Rkabi et al [22]. Moreover, this viscoelastic material depends on the temperature which is supposed to be constant.…”
Section: Modeling Of the Electro-rheological Elastomer Ringmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research work, the ERE material is assumed to be an isotropic material, as proposed by Rkabi et al [22]. Moreover, this viscoelastic material depends on the temperature which is supposed to be constant.…”
Section: Modeling Of the Electro-rheological Elastomer Ringmentioning
confidence: 99%
“…Furthermore, researches on the use of ERE for vibration control of rotor bearing systems are quite rare. Until now and to the knowledge of the authors, there is only a single paper published by Rkabi et al [22] dealing with the application of ERE to control the vibration of a simple Jeffcott rotor using smart ERE supports. The paper discusses the effect of using an ER elastomer bearing insert on the steady-state vibration response and the stability of the rotor system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration performance is one of the most important properties of rolling bearings [1,2], and is the basis for evaluation of bearing life and reliability [3,4]. With progress of manufacturing technology, the machining precision of rolling bearing is continually improving, and lubricating grease becomes an important factor affecting the vibration of bearings [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Zapom el et al (2017) studied the vibration control of rotor by squeeze film damper with magnetorheological fluid (MRF) for vibration suppression of rigid rotors. Rkabi et al (2019) studied the application of smart electrorheological (ER) elastomers to rotor dynamics field to reduce the vibration level of a rotor system. They found that the results reveal by using of the ER elastomer in the conventional journal bearings lead to downshifting of the critical speeds and a considerable reduction in its corresponding vibration amplitude.…”
Section: Introductionmentioning
confidence: 99%